2015
DOI: 10.1002/jso.24113
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of non‐surgical versus surgical therapy for localized hepatocellular carcinoma

Abstract: Non-surgical therapy has become as common as surgery in the treatment of non-cirrhotic, localized HCC. Randomized studies are needed to compare the effectiveness of treatments for this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
0
6
0
2
Order By: Relevance
“…Second, the retrospective nature of the present study and the policies adopted in our centres may have determined a surgical population selection not completely representative of all patients suffering from resectable HCC. However, as previously outlined[ 13 ], patients managed in academic centres are more frequently offered such a potentially curative treatment, and the present data can be considered representative of a tertiary level hospital experience. Finally, limitations of the multivariable competing risk regression model have also to be taken into account.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Second, the retrospective nature of the present study and the policies adopted in our centres may have determined a surgical population selection not completely representative of all patients suffering from resectable HCC. However, as previously outlined[ 13 ], patients managed in academic centres are more frequently offered such a potentially curative treatment, and the present data can be considered representative of a tertiary level hospital experience. Finally, limitations of the multivariable competing risk regression model have also to be taken into account.…”
Section: Discussionmentioning
confidence: 58%
“…Despite the increasing incidence of HCC, the curative approach of hepatic resection remains underused and at times ignored. Recent data from the American College of Surgeons National Cancer Data Base showed that even if hepatic resection was associated with a significant increase in survival among patients with AJCC stage I/II HCC, only less than 40% of such patients were treated surgically[ 13 ]. This proportion increases when patients are managed in academic centres, probably because of a better knowledge of risks and benefits obtainable with hepatic resection[ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Trends over the past decade, analyzed by Mohanty and colleagues from 10,187 total patients with localized, noncirrhotic HCC from the National Cancer Database, reported a decrease in surgical interventions such as resection and transplantation (from 61.6% in 2003 to 44.5% in 2011). 25 During this same time period, the use of nonsurgical therapies increased from 17.2 to 39.2%. Caucasians, higher income, and treatment at an academic medical center were associated with surgical intervention.…”
Section: Trends In Contemporary Management Of Hccmentioning
confidence: 93%
“…Liver resection is one of the potentially curative options for patients with HCC with other modalities, including percutaneous ablation and liver transplantation, for those meeting the criteria. [3][4][5][6][7] Prior literature has shown underutilization of treatment for early-stage disease. 8 There are many considerations when deciding which therapy to pursue, including the severity of underlying liver dysfunction, location and burden of oncologic disease, and the performance status of the patient.…”
mentioning
confidence: 99%